Pain After Forefoot Surgery Comparing Day-Surgery and Conventional Hospitalization: A Continuous Prospective Study of 317 Patients. Issue 1 (19th August 2016) - Besse, Jean-Luc; Chaudier, Philippe; Bourdin, Muriel; Gauthier, Jerome; Fessy, Michel-Henry
Category: Midfoot/Forefoot Introduction/Purpose: At present, there are no guidelines for foot-surgery procedures that can be performed in day-surgery. The aim of our study was to evaluate early postoperative pain after forefoot day-surgery compared to a conventional hospitalization. The hypothesis was that patients operated in day-surgery showed as much pain as those hospitalized, without more complications. Methods: All patients operated for forefoot surgery by one senior surgeon (JLB) were included; those eligible for day-surgery according to SFAR (French Society of Anesthesia and Reanimation) recommendations were operated in day-surgery. Patients were distributed into 4 groups according to surgical procedure: 1.minor procedure (isolated lesser ray) – 2.light (isolated first ray) – 3.intermediate (first ray plus one or two lesser rays) – 4.complex (all forefoot). Patients living alone, further than 50 kilometres from our hospital, or in group 4 were hospitalized for 48 hours. The study included 317 patients; 40% were operated on in day-surgery. Those hospitalized were significantly older (60±3.8 versus 55±3.9, p=0.0006) and with higher ASA scores (p=0.0024) without difference in comorbidity. Main etiology was hallux valgus (70% in both groups); revision surgery counted for 9% of etiologies in the day-surgery versus 14% in the hospitalization group. Results: The highest daily pain rate was on day 1 (4.2/10±2.5 in day-surgery versus 4.4/10±2.4 in hospitalization, p=0.53) without significant difference between groups. Pain was evaluated as extreme (≥8/10) by 9% of patients in day-surgery versus 11% of those hospitalized. We found a statistically significant difference at day 0 for the light surgical procedures (category 2), with higher pain in day-surgery (4.4± 2.4 versus 3.3± 2.5, p=0.02). Concerning anaesthesia, time to recovery of sensitivity after nerve block was comparable regardless of the type of hospitalization or surgical procedure (6.0 hours ± 3.7 in day-surgery versus 5.8 hours ± 5.4, p=0.9). One patient in the day-surgery group had crossover for bleeding. Concerning the self-assessment questionnaire, patients operated in day-surgery described significantly more alertness and attention disturbances following surgery (p=0.01), and more frequent disappearance of pain after day 7 (p=0.02). Conclusion: There was no significant difference in pain or complications between groups. All patients were very satisfied. We can then reasonably recommend performing forefoot day-surgery in good collaboration with the anaesthetist and patient, without exposing the latter to greater pain and further complications.